Increased Pre-Operative Lung Immune Prognostic Index Score Is a Prognostic Factor in Cases of Pathological T3 Renal Cell Carcinoma - Hayato Hoshina; Toru Sugihara; Masayuki Kurokawa; Ei-ichiro Takaoka; Satoshi Ando; Haruki Kume; Tetsuya Fujimura (Current Oncology)
We assessed the efficacy of the lung immune prognostic index (LIPI) in predicting the progression of pathological T3 renal cell carcinoma (RCC). The LIPI scores of patients with pathological T3 RCC were calculated in the pre- and post-operative phases. Patients were divided into zero-point, one-point, and two-point groups according to their LIPI score and into the upstage and non-upstage groups according to the pre- and post-operative increase in LIPI score. Overall survival (OS) was evaluated using Kaplan–Meier curves stratified by group. Univariate and multivariate analyses of OS were performed via Cox proportional hazard regression analysis. LIPI scores were calculated in 80 patients wherein blood sampling data were available. The upstage and non-upstage groups comprised eight and seventy-two patients, respectively. Kaplan–Meier curves showed a significant difference in the pre- to post-operative LIPI score upstage group. LIPI score change was a poor prognostic factor using univariate analysis (OS: hazard ratio (HR) = 4.10, 95% confidence interval (CI) = 1.07–15.61, p = 0.038) and multivariate analysis (OS: HR = 4.38, 95% CI = 1.13–16.89, p = 0.031). An increase in the LIPI score in the pre-operative phase was a poor prognostic factor for pathological T3 RCC.